Penggunaan Microsoft Excel Dalam Penyusunan Laporan Keuangan Untuk Meningkatkan Kualitas Informasi Laporan Keuangan - Triandi, Triandi; Agustin, Marina (Institut Bisnis dan Informatika Kesatuan, 2016)
Compiling a financial reportis important because through this statement both external and internal parties may acquire informations about the firm’s financial conditions and its performance. These informations can then be used to make managerial decision for the sake of the firm’s future. Building an accounting program corresponding to the company’s specific needs can be very expensive and time consuming, not to mention the trials and errors along the way. It takes great efforts to finally come up with ideal accounting program. To solve this issue, Microsoft Excel application provides affordable, simple, fast and accountable accounting program. The aim of this research are to investigate a proper qualitative characteristics of a financial report, to maximize the function of Microsoft Excel application in smaller firms for the purpose of providing a financial statement. The results show that Excel can enchance the informations contained in CV Inovasi Infinita’s financial statements. This application helps with its fast, accurate, complete, user friendly and details. Thus the owner can easily analyse each transaction on the daily basis. The application helps contributing in providing better financial reports.